Therapeutic possibilities of rehabilitation of patients who have undergone COVID-19 with residual changes in the lungs: A review - Galina L. Ignatova; Vladimir N. Antonov (ZAO "Consilium Medicum", 2022)
The article presents data on the mechanisms of formation of preservation of residual changes in lung tissue lesions in patients with a new coronavirus infection COVID-19. The main risk factors leading to the formation of lung tissue damage, such as age, severity of the disease, being on a ventilator, smoking, chronic alcoholism, are considered. The main directions of the search for antifibrotic drugs are presented. The rationale for the use of the pharmaceutical drug Longidaze is given, based on experimental and clinical studies. The main problems faced by doctors during the ongoing COVID-19 pandemic are identified. The schemes of administration of the drug Longidaze in patients with pulmonary fibrosis after a new coronavirus infection are considered.